PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP PRESTASI KERJA KARYAWAN PADA PT BANK PERKREDITAN RAKYAT KOTA MEDAN CABANG ISKANDAR MUDA - Damanik, Lisa Gresti Sella (Bussman Journal : Indonesian Journal of Business and Management, 2024)
This research aims to analyze the influence of compensation and motivation on employee work performance at PT. Rural Credit Bank (BPR) Milala Medan. The method used in this research is the census method with a quantitative approach, namely all employees as the sample. The number of samples used was 36 permanent employees of PT. Rural Credit Bank (BPR) Milala Medan. Data collection techniques by distributing and distributing questionnaires to predetermined samples. Next, it is processed using SPSS (Statistical Program for Social Science) analysis techniques. The results of this research show that (1) compensation has a positive and significant effect on the work performance of PT employees. People's Credit Bank (BPR) Milala Medan, (2) motivation has a positive and significant effect on the performance of PT employees. Rural Credit Bank (BPR) Milala Medan. So it can be concluded that the two independent variables (X1), (X2) have a positive effect on the dependent variable (Y).